Analysis of Employee Placement Based on the Merit System - Yuniarsih, Sy. Eka; Dwimawanti, Ida Hayu; Pribadi, Benny Agus (Adpebi International Journal of Multidisciplinary Sciences, 2024)
This research aims to analyze the suitability of employee placement in the Tanjungpinang City Government based on the merit system. This research is qualitative research using an observation and interview method approach. Information is obtained in more depth and more complete using snowball sampling techniques. The research results show that employee placement in the Tanjungpinang City Government is not in accordance with the merit system. The research results show that there are still problems including; mismatch in educational level, inadequate educational qualifications, less than 1 (one) year of experience in the field, and not/have never taken competency tests and training.